Customer Relationship Management Increasing Curtain Sales with Importance Performance Analysis and Customer Satisfaction Index Methods - Andrian, Reski; Islami, Fajrul; Arlis, Syafri (Universitas Putra Indonesia YPTK Padang, 2025)
The increasingly rapid advancement of technology has an indirect impact on humans. Computers are one of the results of technological advances that can help humans improve the quality and quantity of work. By using computers as one of the tools in presenting data information, especially data processing supported by PHP and MySQL applications, it can support the speed of data processing as efficiently as possible. This study uses the Importance Performance Analysis (IPA) Method and the Customer Satisfaction Index (CSI) Method. The IPA method is a method used to map the relationship between interests and performance of each attribute to meet consumer satisfaction by providing a Likert scale. While the CSI method is a method used to determine the level of consumer satisfaction as a whole by looking at the level of satisfaction of product and service attributes. Based on the combination of the IPA and CSI methods carried out directly in the field using interview techniques, as well as by studying books related to the problems discussed, it is expected that the new system that will be implemented can improve the quality of information so that it can be useful for the relevant agencies. The results of this study are based on the consumer satisfaction index of 82.24% , so that by applying these two methods, it can find consumer satisfaction in increasing curtain sales.